2003
DOI: 10.1161/01.cir.0000050144.67910.13
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Evaluation of the Safety and Efficacy of Enoxaparin Versus Unfractionated Heparin in High-Risk Patients With Non-ST-Segment Elevation Acute Coronary Syndromes Receiving the Glycoprotein IIb/IIIa Inhibitor Eptifibatide

Abstract: Background-Current pharmacotherapeutic options for high-risk non-ST-segment elevation acute coronary syndrome patients include aspirin, clopidogrel, heparin, and platelet glycoprotein IIb/IIIa inhibition. A key issue of uncertainty is the safety and efficacy of combination glycoprotein IIb/IIIa inhibitor and low-molecular-weight heparin therapy. Methods and Results-We randomized 746 patients with rest ischemic discomfort within 24 hours after the onset of symptoms and ST-segment deviation and/or elevation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(82 citation statements)
references
References 30 publications
5
70
1
6
Order By: Relevance
“…Earlier trials (ESSENCE [24], TIMI 11B [19] and INTERACT [25]) showed that enoxaparin resulted in improved clinical outcomes, with no increase or even a reduction in bleeding (25). In contrast, the recent SYNERGY trial (7) showed no benefit, but rather a 17% increase in major bleeding, in patients receiving enoxaparin.…”
Section: Management Strategy and Bleedingmentioning
confidence: 99%
“…Earlier trials (ESSENCE [24], TIMI 11B [19] and INTERACT [25]) showed that enoxaparin resulted in improved clinical outcomes, with no increase or even a reduction in bleeding (25). In contrast, the recent SYNERGY trial (7) showed no benefit, but rather a 17% increase in major bleeding, in patients receiving enoxaparin.…”
Section: Management Strategy and Bleedingmentioning
confidence: 99%
“…38,42 Importantly, enoxaparin was compared with UFH in 746 patients with UA/NSTEMI receiving aspirin and eptifibatide in the Integrilin and Enoxaparin Randomized Assessment of Acute Coronary Syndrome Treatment (INTERACT) trial. 43 The primary endpoint, non-CABG-associated major bleeding, was significantly lower in the enoxaparin compared to the UFH groups (1.8% versus 4.6%), although the relative incidence of minor bleeding was reversed. Also, the rate of death or nonfatal MI at 30 days and of ischemia on a continuous Holter monitor were each reduced almost by half in the enoxaparin group.…”
Section: Lmwhmentioning
confidence: 83%
“…Ischemia on ST-monitoring has been established as an important risk marker in patients with non-ST-elevation ACS [16][17][18][19]. In addition, reductions in Factor Xa inhibition in acute coronary syndromes 445 asymptomatic ischemia have been associated with reductions in other clinically important endpoints [20,21] and have been used to identify patients who benefit from potent or prolonged antithrombotic therapy [22]. In this small sample, differences in baseline characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%